Busy period and busy cycle distributions and parameters for a particular m/g/∞ queue system - Ferreira, Manuel Alberto M. (2013)
Solving a Riccati equation a collection of service times distributions, very general, is determined. For it the M /G /∞ queue busy period and busy cycle probabilistic study, very comfortable, is performed. In addition the properties of that distributions collection are deduced and also presented.